(3GdeUahaGJ s - (3YHO GdYRjR(B, (3TQGHjs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2016)
(3Ef EbJMGe GdeYQaI GdGbJUGOjI h GdGfaUGd ef GdXGgQ Gdi GdLhgQ jJWdH ef GdGbJUGO GdeYGUQ EYOGOG QjGVjG LjOG, h ef Cge GdCOhGJ GdQjGVjI GdJj jfHZj Ydi GdGbJUGOj eYQaJgG h GdJj TGY GSJNOGegG aj GdGbJUGO(B: (3LHQ GdeUahaGJ fXQG deG JJjLg dfG ef GdbOQI Ydi JUhjQ GdYdGbGJ Hjf GdXhGgQ h GdgjGcd GdGbJUGOjI h OjfGejcjJgG YHQ GdRef , Ef GdeUahaGJ hSjdI efXeI dcJGHI GdeYWjGJ GdGbJUGOjI ceG GfgG hSjdI aYGdI h SQjYI dGLQGA GdYedjGJ GdMSGHjI(B.s
(3GdeQGLY U(B.155s
Keywords: (3GdEbJUGO GdQjGVjs; (3GdeUahaGJs